The Manichaean Attitude to Natural Phenomena as Reflected in the Berlin Kephalaia - Kósa, Gábor (Open theology, 2015)
The relationship between religion and science is a hotly debated issue, which has triggered new approaches and redefinitions of fundamental notions worldwide. This paper presents a preliminary sketch of the Manichaean attitude towards natural phenomena, thus exploring the question of the relation of religion to science—even if these notions are not necessarily applicable for early, non-European phenomena—in a historical context. In my survey, I use the Coptic Kephalaia, a fourth-century Manichaean text from Egypt, to highlight some instances (the Sun and the Moon, clouds, vegetation and animals, the salty sea, shadow, and earthquake) that characteristically reflect the unique, early Manichaean attitude to the physical world.